Is There a Solution to Domestic Violence? Digging Deeper Into the Problem of Domestic Violence in Uganda a Case of Ibanda District - Mutabaruka, Fredrick; Kazooba, Charles Tushabomwe (Advances in Social Sciences Research Journal, 2021)
This paper is a deeper analysis to whether there is an end to domestic violence. The fact that there are a numbers of increased cases reported especially during corona virus (covid-19) period, it was inevitable to carry out this study to understand more about domestic violence. The study mainly focused on clear features and causes of domestic violence. It also aimed at coming out with practical approaches to curbing the problem. A mixed design approach was used in both collection and analysis of data. The study used judgmental sampling strategy in selecting the participants because the data that was required more tailored to knowledge based participants. A total of 57 participants were involved from whom interviews and questionnaires were administered. Results reveal a high increase in domestic violence evidenced mainly by assaults of physical, mental emotional and verbal. Other cases are through harassment behaviuors, disrespect and confrontation. The leading caused to domestic violence are attributed to poverty, attitude of male dominance and alcoholism as well as having outside relationships. Creation of extensive public awareness through training and public campaign is recommended as the practical intervention to curb domestic violence.